KONVERGENSI PEREKONOMIAN DI BALI: INEQUALITY SEBAGAI PENYEBAB KEMISKINAN - SURYA DEWI RUSTARIYUNI; NI PUTU WIWIN SETYARI (PIRAMIDA, 2011)
This paper analyze convergenity in economic all of region in Bali. This researchwant to know are they convergentiy in Bali, the disequilibrium growth economic inBali if see from disparity revenue, are they tourism give result for revenue all ofregion in Bali, another variable possible give contribution when convergenityeconomic happen, and calculate time also growth economcy for all of region tocounter the revenue Badung. The method to get result have many step there are: forconvergenity use regression model, to know speed of convergenity use revenue datawith regression and calculate result ?, to know disparity revenue all region use trendvariant from log of revenue and use dummy to see tourism effect, later to calculatetime need all region to counter Badung revenue use compound growth model. Theresult is convergenity doesn’t happen in Bali, use PDB real data and growth economyjust Denpasar can counter Badung revenue as long as 2002-2009 later Jembrana,Karangasem with variation time. Badung and Denpasar become convergenity fastestbeside another region and just Denpasar have ideal growth economy.